2000
DOI: 10.1111/j.1752-1688.2000.tb05707.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF RESIDENTIAL DEVELOPMENT ON GROUND‐WATER QUALITY NEAR DETROIT, MICHIGAN1

Abstract: Two water‐quality studies were done on the outskirts of the Detroit metropolitan area to determine how recent residential development has affected ground‐water quality. Pairs of monitor and domestic wells were sampled in areas where residential land use overlies glacial outwash deposits. Young, shallow waters had significantly higher median concentrations of nitrate, chloride, and dissolved solids than older, deeper waters. Analysis of chloride/bromide ratios indicates that elevated salinities are due to human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 17 publications
(29 reference statements)
2
44
0
Order By: Relevance
“…High level of NO 3 in groundwater can be attributed to seepage from dilapidated septic tanks in residential area or from runoff from agricultural land [30]. They also contribute to high level of chloride, Dissolved solids, sodium, calcium, and potassium to shallow wells [31]. Excess of NO 3 is responsible for methemoglobinemia in infants and also causes physiological distress and bitter taste, among others [23].…”
Section: Resultsmentioning
confidence: 99%
“…High level of NO 3 in groundwater can be attributed to seepage from dilapidated septic tanks in residential area or from runoff from agricultural land [30]. They also contribute to high level of chloride, Dissolved solids, sodium, calcium, and potassium to shallow wells [31]. Excess of NO 3 is responsible for methemoglobinemia in infants and also causes physiological distress and bitter taste, among others [23].…”
Section: Resultsmentioning
confidence: 99%
“…The dilute groundwater end point is represented by a monitoring well (well SO110), which is completed in glacial stratified deposits overlying Mesozoic rocks in a forested, undeveloped area in north-central Connecticut. Groundwater samples from other wells in undeveloped parts of Connecticut (P117) and of the study area (for example, WY86 and WY106) generally had Cl − concentrations less than 10 mg/L and Cl:Br ratios less than 400, which is the ratio that Thomas (2000) considered to be the threshold for anthropogenic sources in the midwestern United States. Cl − and Br − concentrations in shallow groundwater should be similar to those in local atmospheric deposition but slightly more concentrated as a result of evapotranspiration and some interaction with shallow glacial or alluvial deposits.…”
Section: In Milligrams Per Litermentioning
confidence: 97%
“…Groundwater samples that appeared to be affected by road-salt applications and by septic-tank drainfields had the largest deviation from dilute groundwater in the Cl:Br plots. Similarly, in a glacial aquifer in the Detroit, Michigan, metropolitan area, Thomas (2000) found that anthropogenic contaminants were closely related to elevated Cl:Br ratios and surmised that the greatest effect on groundwater quality was from septic-system leachate and from road-salt runoff. Cl − concentrations and Cl:Br ratios for most samples in the study area fall along the mixing curve between typical values for dilute groundwater and road salt ( fig.…”
Section: In Milligrams Per Litermentioning
confidence: 99%
See 1 more Smart Citation
“…Piezometer samples that appeared to be affected by road-salt applications and by septic-tank drainfields had the largest deviation from dilute groundwater in the Cl/Br plots. A median Cl -concentration of 69 mg/L and a Cl/Br ratio of 460, as determined for septic effluent from private septic systems in the midwestern United States (Thomas, 2000;Jagucki and Darner, 2001), were used to represent the end point for septic-system leachate ( fig. 16).…”
Section: Groundwater/surface-water Interactionmentioning
confidence: 99%